TMEM106A mediates atherosclerosis progression through macrophage-centered immune responses and chemokine signaling - Gao, Menglong; Liu, Xingbang; Fang, Zhen; Lun, Jia; Zhang, Qingyun; Zhao, Yunbo; Huang, Yin; Li, Zhenhua (Frontiers in Immunology, 2025)
BackgroundAtherosclerosis (AS) remains a leading cause of cardiovascular morbidity and mortality, characterized by intricate interactions between immune dysregulation and lipid metabolism abnormalities—identifying key mediators in its pathogenesis is critical for improving diagnostics and therapies. This study focuses on Transmembrane Protein 106A (TMEM106A) to clarify its role and clinical relevance in AS progression.MethodsPublic transcriptomic datasets (GSE43292, GSE100927, GSE28829) were analyzed to assess TMEM106A expression and diagnostic value; single-cell RNA-seq data (GSE159677) defined its cellular localization. Immune infiltration (ssGSEA, Cibersort, xCell) and CellChat (intercellular communication) analyses explored its immune associations. In vivo validation used high-fat diet-induced AS in ApoE−/− mice, and in vitro experiments with RAW264.7 macrophages included TMEM106A silencing to test functional effects.ResultsTMEM106A was significantly upregulated in AS samples across datasets, with strong diagnostic efficacy (AUC 0.80–0.95). Single-cell analysis confirmed its specific enrichment in macrophages, with functional links to immune-related pathways. TMEM106A promoted macrophage infiltration, foam cell formation, oxidative stress, and inflammatory responses, while regulating PLCB2 in chemokine signaling; silencing TMEM106A alleviated these pro-atherosclerotic effects.ConclusionTMEM106A contributes to AS progression by modulating macrophage-mediated immune responses and chemokine signaling, as validated in experimental models. These findings support its potential as a clinically relevant biomarker and promising therapeutic target for AS intervention.